Enemies of promise publishing, perishing, and the eclipse of scholarship - Waters, Lindsay (Paradigm, 2004)
"Why books? Lindsay Waters has already sparked a heated debate in the academy, warning that the academic system in the United States, based on the "publish or perish" dictum, is breaking down. In this new pamphlet, Waters brings the debate to a whole new level. He speaks from deep in the heart of the academic machine, as one of the most important and innovative editors in the humanities and social sciences, long witness to the damage the academic world is inflicting upon itself with its unreasonable demands for publication. It is time for scholars to reclaim governance of their own, beloved institutions."--BOOK JACKET.